Exploration geophysics - Gadallah, Mamdouh R.; Fisher, Ray (Berlín : Springer-Verlag, 2010)
Overview of geophysical techiniques -- Seismic fundamentals -- Data acquisition -- Seismic data processing -- Seismic interpretation -- 4-D (time lapse 3-D) seismic surveys -- Future trends.
Incluye índice
Keywords: Geofísica; Magnetismo terrestre; Sismología -- Investigaciones; Sismología -- Mediciones